A multicentre demonstration project to evaluate the effectiveness and acceptability of the web‐based Joint Asia Diabetes Evaluation (JADE) programme with or without nurse support in Chinese patients with Type 2 diabetes. Issue 3 (11th July 2016) - Tutino, G. E.; Yang, W. Y.; Li, X.; Li, W. H.; Zhang, Y. Y.; Guo, X. H.; Luk, A. O.; Yeung, R. O. P.; Yin, J. M.; Ozaki, R.; So, W. Y.; Ma, R. C. W.; et al.
Abstract: Aims: To test the hypothesis that delivery of integrated care augmented by a web‐based disease management programme and nurse coordinator would improve treatment target attainment and health‐related behaviour. Methods: The web‐based Joint Asia Diabetes Evaluation (JADE) and Diabetes Monitoring Database (DIAMOND) portals contain identical built‐in protocols to integrate structured assessment, risk stratification, personalized reporting and decision support. The JADE portal contains an additional module to facilitate structured follow‐up visits. Between January 2009 and September 2010, 3586 Chinese patients with Type 2 diabetes from six sites in China were randomized to DIAMOND ( n = 1728) or JADE, plus nurse‐coordinated follow‐up visits ( n = 1858) with comprehensive assessments at baseline and 12 months. The primary outcome was proportion of patients achieving ≥ 2 treatment targets (HbA1c < 53 mmol/mol (7%), blood pressure < 130/80 mmHg and LDL cholesterol < 2.6 mmol/l). Results: Of 3586 participants enrolled (mean age 57 years, 54% men, median disease duration 5 years), 2559 returned for repeat assessment after a median (interquartile range) follow‐up of 12.5 (4.6) months. The proportion of participants attaining ≥ 2 treatment targets increased in both groups (JADE 40.6 to 50.0%; DIAMOND 38.2 to 50.8%) and there were similar absolute reductions in HbA1c [DIAMOND −8 mmol/mol vs JADE −7 mmol/mol (−0.69 vs −0.62%)] and LDL cholesterol (DIAMOND −0.32 mmol/l vs JADE −0.28 mmol/l), with no between‐group difference. The JADE group was more likely to self‐monitor blood glucose (50.5 vs 44.2%; P = 0.005) and had fewer defaulters (25.6 vs 32.0%; P < 0.001). Conclusions: Integrated care augmented by information technology improved cardiometabolic control, with additional nurse contacts reducing the default rate and enhancing self‐care. (Clinical trials registry no.: NCT01274364) What's new?: The value of quality improvement programmes in the management of chronic conditions has been established in a number of prospective studies and meta‐analyses. The effect of the Joint Asia Diabetes Evaluation (JADE) programme, an information technology‐augmented integrated care model, on diabetes‐related outcomes has been demonstrated in several studies within developed healthcare systems. This study represents one of the few quality improvement initiatives undertaken in a developing country and is the first to answer the question of whether initiatives such as JADE are effective in enhancing quality of care in underfunded healthcare systems. Given the increasing demand for healthcare resources in developing countries, quality improvement has the potential to improve chronic care without substantial additional costs.